Mini-review: Serum immunoglobulins and MASLD - Chen, Ke-qian; Cao, Wen-jing; Wang, Shu-zhi; Li, Wei (Frontiers in Immunology, 2025)
With the development of society and the economy, metabolic dysfunction-associated steatotic liver disease (MASLD) has become a major chronic disease in contemporary society. Finding a safe, effective, and economical diagnostic method is essential for the prevention of MASLD. Serum immunoglobulin is a protein produced by the B cells after the body is stimulated by an external antigen or pathogen. It is very interesting and valuable to explore the relationship between serum immunoglobulins and MASLD. Unfortunately, only a small number of studies have explored the relationship between serum immunoglobulins and MASLD. Therefore, we review the research progress of serum immunoglobulins in MASLD. At the same time, we also discuss the shortcomings of these studies. We hope this review will provide experience and reference for the prevention of MASLD in the future.